Post-Psychedelic Reductions in Experiential Avoidance Are Associated With Decreases in Depression Severity and Suicidal Ideation - Zeifman, Richard J.; Wagner, Anne C.; Watts, Ros; Kettner, Hannes; Mertens, Lea J.; Carhart-Harris, Robin L. (Frontiers in Psychiatry, 2020)
Psychedelic therapy shows promise as a novel intervention for a wide range of mental health concerns but its therapeutic action is incompletely understood. In line with acceptance and commitment therapy’s (ACT’s) transdiagnostic model, qualitative research has suggested that reductions in experiential avoidance are an important component of therapeutic outcomes associated with psychedelics. However, limited research has quantitatively explored the association between decreases in experiential avoidance and therapeutic outcomes associated with psychedelics. Therefore, in two prospective studies, using convenience samples of individuals with plans to use a psychedelic, we explored the impact of psychedelic use on experiential avoidance, depression severity, and suicidal ideation, as well as relationships between changes in these outcomes. Participants (Study 1, N=104; Study 2 N=254) completed self-report questionnaires of depression severity, suicidal ideation, and experiential avoidance: 1) before using a psychedelic (in ceremonial and non-ceremonial contexts), as well as 2) 2-weeks and 3) 4-weeks after psychedelic use. Across both studies, repeated measures ANOVAs indicated significant decreases in experiential avoidance, depression severity, and suicidal ideation after psychedelic use. Furthermore, decreases in experiential avoidance were significantly associated with decreases in depression severity and suicidal ideation. These results suggest that psychedelics may lead to significant decreases in experiential avoidance, depression severity, and suicidal ideation. Additionally, these findings imply that reduced experiential avoidance may be a transdiagnostic mechanism mediating treatment success within psychedelic therapy. We conclude that integrating psychedelics with psychotherapeutic interventions that target experiential avoidance (e.g. ACT) may enhance therapeutic outcomes.